Problems of early learning in foreign language education - Timoshenko, V.I.; Ospanova, V.A. (KSU Publ., 2016)
The article deals with the problems of early English language teaching in foreign language education and their solutions. The authors point out one of the most important tasks of the modern foreign language teachers how to implement effective methods of teaching foreign languages in pre-school children, to raise students' interest to learn the language, enrich the content of education and modernization of the educational process in preschool as a whole. The authors consider difficulties of foreign language teacher, examine psychological and linguistic characteristics of students, and analyze exercises for language skills development of preschool age children, and factual material.
Шет тілдік білім берудегі ерте жастан оқыту мəселелері
Проблемы раннего обучения в иноязычном образовании
Keywords: pre-school age; early education; foreign language education; methods; age features; educational game; types of games; communicative situation